Beryllium-10 dating of Mount Everest moraines indicates a strong monsoon influence and glacial synchroneity throughout the Himalaya - Finkel, R. C.; Owen, L. A.; Barnard, P. L.; Caffee, M. W. (Purdue University, 2003)
Moraine successions in glaciated valleys south of Mount Everest provide evidence for at least eight glacial advances during the late Quaternary. Cosmogenic radionuclide (CRN) surface exposure dating of moraine boulders defines the timing of each glacial advance and refines the previous glacial chronologies. The CRN data show that glaciation was most extensive during the early part of the last glacial (marine oxygen isotype stage [MIS] 3 and earlier), but limited during MIS 2 (the global Last Glacial Maximum) and the Holocene. A previously assumed Neoglacial advance is dated to 3.6 +/- 0.3 ka and the CRN dates confirm a glacial advance ca. 1 ka. These results show that glaciations on the south side of Everest were not synchronous with the advance of Northern Hemisphere ice sheets, yet glaciations within the Himalaya, the world's highest mountain belt, were synchronous during the late Quaternary. The existence of glacial advances during times of increased insolation suggests that enhanced moisture delivered by an active south Asian summer monsoon is largely responsible for glacial advances in this part of the Himalaya. These data allow us to quantify the importance of global climate change and monsoon influence on glaciation in the Himalaya.